Photo-induced transformations in chalcogenide nanocomposite layers - Kikineshi, A.; Malyovanik, M.; Messaddeq, Younes [UNESP]; Pinzenik, V; Shiplyak, M.; Beke, D. L. (Elsevier B.V., 2004)
Investigations of photo-induced structural transformations (PST) and related changes of optical parameters in amorphous chalcogenide layers were further developed towards the establishment of their dependence on the compositional modulation of the material at nanoscale-dimensions (similar to3-10 nm) and possible improvement of optical recording parameters as well. Besides the known amorphous-amorphous PST, photo-stimulated interdiffusion and crystallization in multilayer structures were found as a useful method for amplitude-phase optical relief formation. The last two types of PST were influenced by size restrictions and efficiently operated by the composition and by the modulation period of the layered nanocomposite. Experimental evidences were obtained in Se-, AsSe-, Se0.4Te0.6-containing layered or quasi zero-dimensional structures based on As2S3 or SiOx and MgF2 matrix. Comparison was made with As2S3- and GeS2-based multicomponent layers, containing Se, Te and Ga. (C) 2004 Elsevier B.V. All rights reserved.